The Relationship Between Personal Character Types With Leadership Style (Case Study: Managers Of State Organizations In Bushehr Province) - Nia, Ehsan Razmi; Nia, Abdol Reza Beygi (The Turkish Online Journal of Design Art and Communication, 2016)
This study aimed to identify "the relationship between Personal Character types with leadership style". Based on the formula limited sampling (Cochran), the sample comprised 100 people from the population of the study (including all public organizations managers of Bushehr province) were selected. The data related to variables of types character and leadership styles were measured with questionnaires measuring personality and leadership style. Of expert opinions (professors of management, pedagogy and psychology) to ensure the validity of both questionnaires and thus confirmed the validity and Cronbach's alpha coefficient was calculated by the pilot. After distributing and collecting the questionnaires, the Pearson correlation coefficient test for the presence or absence of a relationship between variables was performed. Results obtained of data analysis using SPSS software showed a significant relationship between variables. MANOVA test results also show that there is a significant relationship between demographic variables (management experience and work experience) with the leadership styles of managers. Also results of this study showed a significant relationship between the two variables with leadership style.
Keywords: Personality; Type of Personality; Leadership; Leadership Styles